PENGETAHUAN IBU MENYUSUI TENTANG TEKNIK MENYUSUI YANG BENAR - Agustina, Eka; Pane, Efi Irwansyah (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Correct breastfeeding technique is a crucial factor in the success of exclusive breastfeeding and the prevention of complications such as sore nipples or engorgement. This study aims to determine the level of knowledge of breastfeeding mothers regarding proper breastfeeding techniques in Karang Baru Village. The research method used was descriptive quantitative. The population in this study was all 29 breastfeeding mothers in Karang Baru Village. The sampling technique used purposive sampling, resulting in a sample of 21 respondents. The data collection instrument used a structured questionnaire covering breastfeeding position, baby attachment, and release techniques. The results showed a diverse distribution of respondents' knowledge levels, with 69.3% of respondents with sufficient knowledge. This finding indicates that the majority of breastfeeding mothers in the study area still have less than optimal or uneven knowledge. The lack of information regarding lactation management is a major obstacle to implementing proper breastfeeding techniques. The conclusion of this study is that the low percentage of those with sufficient knowledge requires an active role for health workers in providing ongoing education. It is recommended that village midwives and health cadres conduct practical demonstrations of breastfeeding techniques regularly to improve mothers' skills and confidence in breastfeeding.